Career indecision among Malaysian final year students: self-efficacy, decision-making styles, planned happenstance skills - Chong, Hoi Yan; Tan, Russell Tzen Qian (2019)
The circumstances where individuals are incapable of taking a career decision they aspire is known as career indecision. Prior studies indicated several individual characteristics that are connected to career indecision, however, these studies yielded inconsistent results and the information on whether avoidant and spontaneous decision-making styles, and planned happenstance skills (PHS) are associated with individuals’ career indecision is sparse. The current study aims to understand the relationships between career indecision and self-efficacy, decision-making styles, and PHS among Malaysian final year students. With the employment of cross-sectional research design together with purposive sampling method, 589 respondents were recruited through both online and paper-and-pencil survey methods. However, only 380 of them have completed the questionnaire and fulfilled the criteria of (1) studying at local universities; (2) currently a final year student. Career Decision-making Difficulties Questionnaire (CDDQ), General Self-efficacy Scale (GSE), General Decision Making Style Test (GDMS), and Planned Happenstance Career Inventory (PHCI) were used to measure desirable variables. The correlation analysis indicated that career indecision is negatively associated with self-efficacy, optimism and persistence, while positively associated with intuitive, dependent, spontaneous and avoidant decision-making styles. Besides, career indecision was found of no relation with rational decision-making style, flexibility, curiosity, and risk-taking. The results of the current study would contribute to the literature of career indecision in the Malaysian context, and provide useful implications to relevant mental health professionals in implementing effective interventions for final year Malaysian students, to make a career related decision.